PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM DAN BRAND AWARENESS TERHADAP NIAT BELI KONSUMEN PADA PROJECT BISNIS ILOCHA.ID: PENGARUH SOCIAL MEDIA MARKETING INSTAGRAM DAN BRAND AWARENESS TERHADAP NIAT BELI KONSUMEN PADA PROJECT BISNIS ILOCHA.ID - Stelson, Brellian rachel; Setyawati, Christina Yanita (Universitas Ciputra Surabaya, 2025)
The study aims to analyze the influence of Social Media Marketing Instagram and Brand Awareness on Consumer Purchase Intention for Ilocha.id products. Ilocha.id, a food and beverage business, utilizes Instagram as its primary marketing platform to engage consumers through creative content, paid advertising, and interactive campaigns. The study employs a quantitative explanatory approach, using a sample of 120 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS software. The results reveal that Social Media Marketing Instagram significantly influences Consumer Purchase Intention, with a positive coefficient indicating that improved marketing strategies, such as visually appealing content and prompt responses, increase consumer interest. Similarly, Brand Awareness significantly impacts purchase intention, demonstrating that brand recognition, recall, and perceived quality drive consumer trust and decision-making. The findings underscore the importance of integrating social media marketing strategies with efforts to strengthen brand awareness to achieve a competitive advantage. Ilocha.id is advised to optimize Instagram features like reels, live streams, and collaborations with influencers while maintaining a consistent brand identity. Future studies should expand sample sizes and consider additional variables, such as pricing and consumer reviews, to gain a broader understanding of purchase intention drivers. Keywords: Social Media Marketing, Instagram, Brand Awareness, Consumer Purchase Intention.